Mosaici di epoca romana a Matelica (MC) - Santucci, Martina (O T I V M, 2019)
After an historical and topographical introduction of Matelica as a roman context, this work presents an excursus on mosaics found within the limits of the ancient municipium. This paper also provides information about floors and tiles measurements, as well as about mosaics’ patterns, being possibly compared one to each other. The historical context resulting from the analysis of such numerous data, is complex and multi-layered. It reaches its apex during the first imperial age, when huge domus were built, enriched by painted plasters as well as by geometric and figurative mosaics. These manufactures’ value does not just depend on the quality of building materials, but also on the iconographies selected by a high-level clientele.